PENGAWASAN PARTISIPATIF MASYARAKAT UNTUK MEWUJUDKAN PEMILU JUJUR DAN ADIL - Suryadi, Mohammad Anton (STIH Zainul Hasan Kraksaan Kraksaan, 2023)
Abstrack Community participatory supervision as an effort to realize honest and fair general elections is urgently needed to ensure transparency, accountability and integrity in the administration of elections. The essence of the people as holders of electoral sovereignty guaranteed by the constitution has the right not only to elect leaders directly, but also the right to supervise that elections are held without fraud, intimidation or unhealthy political influence. The practice of money politics that often occurs in election contests results in the degradation of democracy in selecting leaders. In the context of democracy, elections are important moments whose integrity must be maintained in order to represent the people's voice in a real way, so that elections are able to realize the people's aspirations to have leaders who have integrity, are competent and are not corrupt. Therefore, community participatory supervision is considered as a form of social control that can monitor and ensure the integrity of elections. Keywords: Monitoring, Community, Election.